Leishmania infantum and Leishmania braziliensis: Differences and Similarities to Evade the Innate Immune System - Falcão, Sarah de Athayde Couto; Jaramillo, Tatiana M. G.; Ferreira, Luciana G.; Bernardes, Daniela M.; Santana, Jaime M.; Favali, Cecília B. F. (Frontiers in Immunology, 2016)
Visceral Leishmaniasis is a severe form of the disease, caused by Leishmania infantum in the New World. Patients present an anergic immune response that favors parasite establishment and spreading through tissues like bone marrow and liver. On the other hand, Leishmania braziliensis causes localized cutaneous lesions, which can be self healing in some individuals. Interactions between host and parasite are essential to understand disease pathogenesis and progression. In this context, dendritic cells (DCs) act as essential bridges that connect innate and adaptive immune responses. In this way, the aim of this study was to compare the effects of these two Leishmania species, in some aspects of human dendritic cells biology to better understanding of the evasion mechanisms of Leishmania from host innate immune response. To do so, DCs were obtained from monocytes from whole peripheral blood’s healthy volunteers donors and infected with L. infantum or L. braziliensis for 24 hours. We observed similar rates of infection (around 40%) as well as parasite burden for both Leishmania species. Concerning surface molecules, we observed that both parasites induced CD86 expression when DCs were infected for 24h. On the other hand, we detected a lower surface expression of CD209 in the presence of both L. braziliensis and L. infantum, but only the last one promoted the survival of dendritic cells after 24 hours. Therefore, DCs infected by both Leishmania species showed a higher expression of CD86 and a decrease of CD209 expression, suggesting that both enter DCs through CD209 molecule. However, only L. infantum had the ability to inhibit DC apoptotic death, as an evasion mechanism that enables its spreading to organs like bone marrow and liver. Lastly, L. braziliensis was more silent parasite, once it did not inhibit DC apoptosis in our in vitro model.